Diagnosis delayed: health profile differences between women with undiagnosed polycystic ovary syndrome and those with a clinical diagnosis by age 35 years. Issue 8 (8th May 2021) - Fernandez, Renae C; Moore, Vivienne M; Rumbold, Alice R; Whitrow, Melissa J; Avery, Jodie C; Davies, Michael J
Abstract: STUDY QUESTION: Are reproductive, metabolic or psychological health profiles of women with clinically diagnosed polycystic ovary syndrome (PCOS) different from those with undiagnosed PCOS? SUMMARY ANSWER: Obtaining a clinical diagnosis of PCOS is strongly linked to the experience of fertility problems, but not clinical depression or poor metabolic health, although these were highly prevalent in women with PCOS irrespective of when they were diagnosed. WHAT IS KNOWN ALREADY: PCOS is an endocrine disorder that is relative common, but heterogeneous in presentation. This may impact on the pathways to diagnosis and timely treatment. STUDY DESIGN, SIZE, DURATION: A cross-sectional analysis of a community-based cohort of 974 women, established retrospectively when women were around 30 years of age. PARTICIPANTS/MATERIALS, SETTING, METHODS: In this cohort of women born in Adelaide, South Australia, half of women who met the Rotterdam criteria for PCOS were previously undiagnosed. We compared women with prior clinical diagnosis of PCOS, those diagnosed through participation in this research, and the remainder in the cohort. Sociodemographic characteristics, reproductive, metabolic and psychological health, including medical conditions and medications were considered. Logistic regression was undertaken to identify independent predictors of prior clinical diagnosis. MAIN RESULTS AND THE ROLE OF CHANCE: There were 56 women with a prior clinical diagnosis of PCOS (5.7%) and a further 64 (6.6%) were undiagnosed until study entry. The great majority of women with a prior diagnosis of PCOS reported having had problems with periods (95%) and excess body hair (63%). Corresponding proportions for women undiagnosed until study participation were slightly lower (81% and 45%, respectively). Although the proportion of women attempting or achieving pregnancy was similar across all groups, those with a prior diagnosis of PCOS were four times more likely to have reported difficulties becoming pregnant than those undiagnosed (odds ratio = 4.05, 95% CI 1.74–9.45) and frequently sought medical assistance. Metabolic problems were higher in both PCOS groups compared to women without PCOS. In both PCOS groups, the prevalence of clinical depression was 50% higher than in those with no PCOS ( P  = 0.021). LIMITATIONS, REASONS FOR CAUTION: The number of women who were diagnosed with PCOS both prior to and during the study limited statistical power available to detect modest differences between the PCOS groups. Some women in the group classified as not having PCOS may have remained undiagnosed, but any bias from this source would contribute to more conservative findings. WIDER IMPLICATIONS OF THE FINDINGS: Findings reinforce the need for early detection of PCOS symptoms from adolescence, ensuring timely diagnosis and appropriate health care. The high prevalence of depression among clinically diagnosed and undiagnosed women with PCOS suggests this is a feature of the condition and supports recent recommendations in the international PCOS guidelines to screen all women with PCOS for depression and anxiety. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by a project grant (2017) from the National Health and Medical Research Council of Australia (NHMRC) Centre for Research Excellence in Polycystic Ovary Syndrome (Grant ID APP1078444). R.C.F. and J.C.A. were supported by Robinson Research Institute Lloyd Cox Career Development Fellowships (2018). Establishment of the cohort was funded by an NHMRC Strategic Award No. 465455, a Career Development Award in Population Health (No. 349548) and the Australian Research Council (Future Fellowship FT100101018) awarded to M.J.D. All authors declared no conflict of interest. TRIAL REGISTRATION NUMBER: N/A.